Bank Differences in the Coordination of Regulatory Capital, Earnings, and Taxes - Collins, Julie H.; Shackelford, Douglas A.; Wahlen, James M. (Journal of Accounting Research, 1995)
Banking, Regulatory capital, Financial reporting, Tax incentives